2013
DOI: 10.1016/j.yexmp.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular, but not parenchymal, cerebral engraftment of donor cells after non-myeloablative bone marrow transplantation

Abstract: Myeloablative (MyA) bone marrow transplantation (BMT) results in robust engraftment of BMT-derived cells in the central nervous system (CNS) and is neuroprotective in diverse experimental models of neurodegenerative diseases of brain and retina. However, MyA irradiation is associated with significant morbidity and mortality and does not represent a viable therapeutic option for the elderly. Non-myeloablative (NMyA) BMT is less toxic, but it is not known if the therapeutic efficacy observed with MyA BMT is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Our observations that BM chimerism following submyeloablative chemotherapy using BU result largely in perivascular BMDC accumulation in the cerebral cortex and hippocampus are consistent with our previous observations in spinal cord tissue [11], as well as several recent studies [10,28]. Yang et al, compared the effects of myeloablative and submyeloablative irradiation with those of chemotherapy (fludaribine and cyclophosphamide), either alone or with submyeloablative irradiation [28]. The authors claim that significant parenchymal BMDC engraftment of brain does not occur with irradiation less than 5 Gray and that even at this irradiation dose, BMDCs are almost exclusively perivascular monocytes.…”
Section: Bone Marrow-derived Cells In Brainsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations that BM chimerism following submyeloablative chemotherapy using BU result largely in perivascular BMDC accumulation in the cerebral cortex and hippocampus are consistent with our previous observations in spinal cord tissue [11], as well as several recent studies [10,28]. Yang et al, compared the effects of myeloablative and submyeloablative irradiation with those of chemotherapy (fludaribine and cyclophosphamide), either alone or with submyeloablative irradiation [28]. The authors claim that significant parenchymal BMDC engraftment of brain does not occur with irradiation less than 5 Gray and that even at this irradiation dose, BMDCs are almost exclusively perivascular monocytes.…”
Section: Bone Marrow-derived Cells In Brainsupporting
confidence: 92%
“…Cells having an amoeboid morphology were notably absent, further supporting the claim that this morphology of BMDC is related to irradiative treatment [6,11,27]. Our observations that BM chimerism following submyeloablative chemotherapy using BU result largely in perivascular BMDC accumulation in the cerebral cortex and hippocampus are consistent with our previous observations in spinal cord tissue [11], as well as several recent studies [10,28]. Yang et al, compared the effects of myeloablative and submyeloablative irradiation with those of chemotherapy (fludaribine and cyclophosphamide), either alone or with submyeloablative irradiation [28].…”
Section: Bone Marrow-derived Cells In Brainsupporting
confidence: 91%
“…We have shown in mice that, although non-myeloablative BMT engrafts the periphery with efficiency of about 90% at 8 months post transplant, it does not engraft brain. 81 There are no data on the interactions between peripheral and central progranulin, so we cannot predict the likelihood that non-myeloablative BMT might ameliorate biochemical deficits in cerebral cortex of Grn −/− mice or behavioral changes in Grn +/− mice; these complicated experiments are underway.…”
Section: Discussionmentioning
confidence: 99%
“…These assumptions were made on the basis of cell transplantation experiments in rodents starting in the 1980s 9, 10 . Just recently, chemotherapeutical conditioning additionally suggested that perivascular macrophages were present in the CNS parenchyma after BM transplantation 11, 12 . However, all of these studies used either irradiation or chemotherapy as conditioning regimens thereby inducing an artificial influx of injected BM-derived cells due to damage of the blood-brain barrier and local induction of chemoattractants in the host CNS 1315 .…”
Section: Introductionmentioning
confidence: 99%